2019
DOI: 10.1186/s12889-019-7867-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health education intervention on knowledge and perception of cervical cancer and screening for women in Ghana

Abstract: BackgroundThe burden of cervical cancer continues to rise in developing economies. Women in the sub-Saharan African region have higher chances of developing cervical cancer due to a greater prevalence of related risk factors. The purpose of this study was to determine the effect of health education intervention on cervical cancer and screening perceptions of women in the Komenda, Edina, Eguafo, and Abirem (K.E.E.A) District in the Central Region of Ghana.MethodsA non-equivalent control-group design was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 23 publications
3
44
0
4
Order By: Relevance
“…The results indicated an increase in the performance of Pap smear test after the intervention. Although the utilized method was different from that employed in the present study, the results con rmed the positive effect of educational interventions on promotion of cancer prevention methods among women(19).…”
supporting
confidence: 43%
See 1 more Smart Citation
“…The results indicated an increase in the performance of Pap smear test after the intervention. Although the utilized method was different from that employed in the present study, the results con rmed the positive effect of educational interventions on promotion of cancer prevention methods among women(19).…”
supporting
confidence: 43%
“…Ebu et al (2019) assessed the impact of planned interventions based on the health belief model on breast cancer and cervical cancer screening as well as performance of the Pap smear test among 870 women. The results indicated an increase in the performance of Pap smear test after the intervention.…”
mentioning
confidence: 99%
“…Implementation of an effective colorectal cancer screening program has the potential to make a significant impact on the burden of disease as many colorectal cancers are curable if detected early and preventable if excised at the pre-malignant stage [ 5 , 6 ]. Unfortunately, nationwide cancer screening efforts remain a significant challenge in Ghana, even with more prevalent diseases such as prostate, breast and cervical cancers [ 3 , 7 , 8 ]. There is limited data available on current Ghanaian colorectal cancer screening practices and no data regarding barriers to screening despite the establishment of national guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we sought to better understand the current colorectal cancer screening practices of Ghanaian physicians across several different specialties. We hypothesized that, similar to breast and cervical cancer screening, there exist many physician-, patient- and system-level barriers that prevent widespread colorectal cancer screening and uptake of the national guidelines [ 7 , 8 ]. Identification of these barriers is necessary to improve screening and ultimately increase early detection, prevention and cure of colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…With this device we achieved the use of time in waiting rooms with cervical cancer prevention education while the women had their turn to be seen by the clinicians. Previous scientific literature has shown that low level of awareness and knowledge about the disease and its early detection are factors that affect the use of Pap tests [97,98], and that health education through lectures, debates, videos and brochures is essential to improve cervical cancer screening [99]. We have incorporated into the wireless queuing device an App that included a risk survey, finding that women with high perceived susceptibility were those who underwent cytology after being exposed to a 'Tu Turnero ESE '.…”
Section: Plos Onementioning
confidence: 99%